Penyuluhan Pentingnya Mengonsumsi Ikan Sebagai Sumber Protein Sejak Usia Dini - Hairulaila; Anggi; Salman Al Farisy; Abdurrahman (Jurnal Pengabdian Kepada Masyarakat Multi Disiplin, 2025)
Fish consumption from an early age plays a crucial role in supporting children's growth and development, particularly in the development of intelligence, bone health, and immunity. However, fish consumption among elementary school-aged children remains relatively low due to a lack of knowledge and undeveloped consumption habits. This outreach program aims to educate, raise awareness, and provide understanding to young children about the importance of consuming fish as a source of protein and essential nutrients for the body. The method used in this activity was a lecture and question-and-answer session. Evaluation was conducted using pre- and post-tests to measure changes in students' knowledge levels before and after the outreach program. The results showed an increase in students' knowledge regarding the nutritional benefits of fish and the importance of regular fish consumption for health and intelligence. The increase in post-test scores compared to the pre-test indicates that the outreach program was effective in improving students' understanding. Therefore, outreach programs on the importance of consuming fish from an early age need to be conducted sustainably and involve various parties, including schools and families.